Tax Law Perspectives on Tax Amnesty Policy Assessment: Balancing Fairness and Compliance - Siti Nurjannah Lase; Shafa Zhafira Khalid; Zahara Ananda; Mufqi Aulia; David Nwanna Dumbiri (ISNU Sumatera Utara, 2025)
The tax amnesty policy is a strategic step taken by the Indonesian government to improve taxpayer compliance and expand the tax revenue base through tax amnesty by providing an opportunity to report unreported assets without administrative or criminal sanctions. This study aims to analyze the assessment of the tax amnesty policy from a tax law perspective, particularly in balancing the principles of fairness and tax compliance. The method used is a socio-legal approach with a literature study on the regulation and implementation of tax amnesty and its impact on social justice and taxpayer compliance. The results show that the success of this policy is highly dependent on the government's ability to implement a fair and transparent amnesty mechanism without sacrificing justice for compliant taxpayers. In addition, the effectiveness of the tax amnesty program is also influenced by the level of legal certainty, political stability, and ease of tax administration to encourage a culture of voluntary compliance. Therefore, the assessment of the tax amnesty policy must consider the balance between state revenue and social justice in order to create a sustainable and trusted tax system